Advancements in hydrogel design for articular cartilage regeneration: A comprehensive review - Fariba Hashemi-Afzal; Hooman Fallahi; Fatemeh Bagheri; Maurice N. Collins; Mohamadreza Baghaban Eslaminejad; Hermann Seitz (Bioactive Materials)
This review paper explores the cutting-edge advancements in hydrogel design for articular cartilage regeneration (CR). Articular cartilage (AC) defects are a common occurrence worldwide that can lead to joint breakdown at a later stage of the disease, necessitating immediate intervention to prevent progressive degeneration of cartilage. Decades of research into the biomedical applications of hydrogels have revealed their tremendous potential, particularly in soft tissue engineering, including CR. Hydrogels are highly tunable and can be designed to meet the key criteria needed for a template in CR. This paper aims to identify those criteria, including the hydrogel components, mechanical properties, biodegradability, structural design, and integration capability with the adjacent native tissue and delves into the benefits that CR can obtain through appropriate design. Stratified-structural hydrogels that emulate the native cartilage structure, as well as the impact of environmental stimuli on the regeneration outcome, have also been discussed. By examining recent advances and emerging techniques, this paper offers valuable insights into developing effective hydrogel-based therapies for AC repair.